2014
DOI: 10.3368/er.32.1.46
|View full text |Cite
|
Sign up to set email alerts
|

Soft Shell Clams (Mya arenaria) Contribute to Macroalgal Blooms in a Partially-restored Gulf of Maine Back-barrier Lagoon

Abstract: Like many Eastern US salt marshes, East Harbor salt marsh lagoon on Cape Cod was isolated from tidal flow in the 1800s, resulting in near-freshwater conditions and loss of native salt marsh species. After partial restoration in 2002, salt marsh species recolonized East Harbor, and soft shell clam (Mya arenaria) recolonization was prolific, with peak densities reaching 3,200 individuals m -2 in 2005. However, severe macroalgal blooms in 2006-2007 resulted in anoxia and mortality of benthic organisms (including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…littorea , have been largely absent from the East Harbor Main Lagoon (where algal blooms are most extensive) owing to high summer water temperatures (Smith et al ). Thiet et al () also observed that the presence of L . littorea significantly reduced macroalgal growth in experimental mesocosms.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…littorea , have been largely absent from the East Harbor Main Lagoon (where algal blooms are most extensive) owing to high summer water temperatures (Smith et al ). Thiet et al () also observed that the presence of L . littorea significantly reduced macroalgal growth in experimental mesocosms.…”
Section: Discussionmentioning
confidence: 87%
“…A recent study at East Harbor (Thiet et al ) suggests that rapid and prolific recolonization of East Harbor by mollusks following tidal restoration directly contributed to the algal blooms of 2005–2006, resulting in a negative feedback on molluscan richness and density. In that study, M .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations